Human Resource Management at the Integrated Islamic School Robbani Ogan Ilir - Abadi, Sapto; Fitria, Happy; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2024)
By concentrating on recruitment, selection, placement, training, development, compensation, and evaluation, this study aims to investigate the implementation of human resource planning, recruitment, training, compensation, and management assessment at the Robbani Integrated Islamic School. South Sumatra’s Robbani Ogan Ilir Integrated Islamic School served as the site of this qualitative study. The topic was the person being interviewed, and the researcher was the primary tool. Field notes, papers, and interview scripts were used to gather data. In-depth interviews, participant observation, and recording were the main methodologies employed in the study, which took a cyclical, meaning-based, and emic viewpoint approach. Data reduction, presentation, and conclusion strategies were used in data analysis. The findings of a study on human resource management at SIT Robbani Ogan Ilir highlight several key elements, including systematic recruitment, training, compensation, and assessment as well as strategic development planning. Core skills are the focus of the Robbani People Development Program. Contract employees are paid a set wage, while permanent employees are paid a regular salary. Compensation is differentiated based on job status. Additionally used are performance review and evaluation management.